2000
DOI: 10.1080/10934520009377037
|View full text |Cite
|
Sign up to set email alerts
|

Retrofitting a stormwater management facility with a wetland component

Abstract: The City of Toronto has built a stormwater management system, the Etobicoke Stormwater Management Facility (ESWMF), along the Lake Ontario shoreline. The Facility represents an innovative stormwater management solution that integrates two previously separate water quality improvement technologiesstormwater wetlands and flow balancing systems. The facility, besides improving water quality, will provide aesthetic, recreational and educational benefits. A conceptual plan to retrofit a wetland component within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…They represent a means of potentially improving the treatment performance of the conventional pond systems by integrating the beneficial aspects of emergent macrophytes without being constrained by the requirements of shallow water depth (Dalu et al 2012;Wanda et al 2015). Similarly, they also offer some advantages over the conventional sedimentrooted wetlands such as their ability to cope up with variable water depths that are typical of any event-driven storm water system (Kerr-Upal et al 2000;Manyumba et al 2009;Srivastava et al 2014Srivastava et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They represent a means of potentially improving the treatment performance of the conventional pond systems by integrating the beneficial aspects of emergent macrophytes without being constrained by the requirements of shallow water depth (Dalu et al 2012;Wanda et al 2015). Similarly, they also offer some advantages over the conventional sedimentrooted wetlands such as their ability to cope up with variable water depths that are typical of any event-driven storm water system (Kerr-Upal et al 2000;Manyumba et al 2009;Srivastava et al 2014Srivastava et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The thick networks of roots and associated biofilms have proven to be effective in physically trapping particulates within the water column, which subsequently slough off the roots as heavier particles settle. FTWs have been studied for many decades all over the world for their application in water quality improvement and storm water control (e.g., Revitt et al 1997;Kerr-Upal et al 2000), combined stormwater and sewer overflow (e.g., Van Acker et al 2005), sewage treatment (e.g. Ghobrial and Siam 1998;Ash and Truong 2003;Todd et al 2003), acid mine drainage treatment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile plants are established directly into this floating matrix, and the roots grow into the water column below (Figure 2). Studies undertaken in the United States and New Zealand [10][11][12][13][14][15][16] have found that FTW can provide an effective, low cost, and low maintenance means of treating domestic and agricultural Contemporary artificial FTWs are typically constructed using a combination of woven plastic, organic based matting, and fibreglass [8,10]. Juvenile plants are established directly into this floating matrix, and the roots grow into the water column below (Figure 2…”
Section: Introductionmentioning
confidence: 99%
“…As FTWs do not require additional earthworks or land uptake, they can also offer increased pollution removal performance at a substantially lower cost compared to alternatives such as constructed wetlands. Contemporary artificial FTWs are typically constructed using a combination of woven plastic, organic based matting, and fibreglass [8,10]. Juvenile plants are established directly into this floating matrix, and the roots grow into the water column below (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation